Rancang Bangun Kapal Perikanan Purse Seine Fiber Glass Pada Industri Kapal PT. Carita Boat Indonesia (CBI) Suatu Analisis Naval Arsitek - A. Masyahoro (Universitas Tadulako, 2006)
This study was intended to explore the technical feasibility using a naval analysis technique of a purse seine boat architecture with a capacity of 30 GT and produced by PT. Carita Boat Indonesia (CBI). Data collected were the boat main measures and hydrostatic parameters which were collected through survey and direct observation. Mathematic calculations indicated that the G point was below that of M, meaning that the righting arm value or the GZ will be positive. This positive GZ value will enable the boat to return back to normal position known as stable equilibrium after external disturbances. Based on the static stability standards of the purse seine KGAD and GM, this boat has met the standard criteria. Other calculations made in this study and now reported are the value of heaving amplitude and the `koper encounter frequency at following seas using a simulation technique. This was done on 3 different LwiLs ratios (0.5, 1.0 and 1.5) and 6 different boat velocities, m/see (2.574, 3.089, 3.604,4.118, 4.633 and 5.148).